Estudio de Dinamica de Agregacion proteica con TRP-Cage - Faundez, Cristian Leonel (2018)
We studied by molecular dynamics (MD) aggregating two mini proteins such as TRP-cage (TRP) in neutral pH conditions and with explicit solvent. The results correspond to two different systems, the first with 3952 water molecules and one TRP and the second with 7654 water molecules and two TRPs. Both systems were simulated in NVT and NPT ensembles, with T = 300 K and P = 1 bar. The results show the formation of stable dimers in short simulation times. The analyzes made from the surface accessible to the solvent show that the main mechanism or driver of the formation of these dimers at neutral pH is the hydrophobic interaction between different sectors of the protein (hydrophobic amino acids). Keywords: Proteins,TRP-cage,Solvent Accessible Surface(SASA).